Effectiveness of the Sustainable Food Yard Program (P2L) in Active Groups in Madiun City: Evaluation Based on Technical Instructions: Efektivitas Program Pekarangan Pangan Lestari (P2L) pada Kelompok Aktif di Kota Madiun: Evaluasi Berdasarkan Petunjuk Teknis - Shavira Yumna; Syarif Imam Hidayat; Fatchur Rozci (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
Food consumption diversification is a crucial effort to achieve food security and improve public nutrition in urban areas. The Sustainable Food Yard (P2L) program was initiated as a strategic policy to enhance food availability, accessibility, utilization, and household income through optimizing yard land. This study aimed to analyze the effectiveness of the P2L Program in Madiun City based on these four indicators. Using a quantitative descriptive approach with a survey method, sampling employed Proportional Stratified Random Sampling resulting in 80 respondents. The unit of analysis was limited to 15 active P2L groups out of 58 registered groups in Madiun City. Data were collected through questionnaires, interviews, and observations, then analyzed using effectiveness achievement percentages. Results showed that the average effectiveness of the P2L Program among active groups was in the highly effective category (87.64%). Food accessibility recorded the highest score (93.25%), followed by household income (87.38%), food availability (85.13%), and food utilization (84.80%). The high achievement in accessibility demonstrates that the program successfully brings food sources directly to the household level. However, these findings are limited to active groups serving as a best practice model and thus do not reflect the condition of the other 43 unproductive groups. Kata kunci: Ketahanan pangan; Pekarangan Pangan Lestari; Efektivitas; Pemanfaatan Pekarangan